2007
DOI: 10.1152/ajpendo.00616.2006
|View full text |Cite
|
Sign up to set email alerts
|

Impaired adaptation to repeated restraint and decreased response to cold in urocortin 1 knockout mice

Abstract: ) is a corticotropin-releasing factor (CRF)-like peptide whose role in stress is not well characterized. To study the physiological role of UCN1 in the response of the hypothalamic-pituitary-adrenal (HPA) axis to stress, we generated UCN1-knockout (KO) mice and examined their adaptation to repeated restraint and to cold environment. Wild-type (WT) and UCN1-KO animals were restrained hourly for 15 min from 9 AM to 2 PM, and blood samples were obtained for corticosterone measurement. WT animals adapted to repeat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“…Urocortin is thought to be involved in the autonomic stress response [53] but so far studies with knockout mouse models have revealed no consistent evidence for an involvement of urocortin in the HPA axis response to acute stress (reviewed in [54]). The study of Zalutskaya et al [55] on the response of urocortin knockout mice to repeated restraint indicates that urocortin may play a role in the adaptation of the HPA axis to chronic stress. Little is known about the function of urocortin in the pig.…”
Section: Resultsmentioning
confidence: 99%
“…Urocortin is thought to be involved in the autonomic stress response [53] but so far studies with knockout mouse models have revealed no consistent evidence for an involvement of urocortin in the HPA axis response to acute stress (reviewed in [54]). The study of Zalutskaya et al [55] on the response of urocortin knockout mice to repeated restraint indicates that urocortin may play a role in the adaptation of the HPA axis to chronic stress. Little is known about the function of urocortin in the pig.…”
Section: Resultsmentioning
confidence: 99%
“…Whereas Wang and colleagues (Wang et al, 2002) reported no differences in anxiety-like behaviors, Vetter and colleagues (Vetter et al, 2002) reported increased anxiety-like behaviors in the EPM and OF, but not in the DLT, tests. In a more recently developed Ucn1-KO line a slightly increased glucocorticoid response to an intermittent restraint stress in male (but not female) mice was reported (Zalutskaya et al, 2007). …”
Section: Role Of Urocortins In Adaptation To Stress and Anxiety: Genementioning
confidence: 99%
“…An increasing body of evidence indicates that Ucn1 plays a role in stress adaptation (Skelton et al, 2000; Gysling et al, 2004; Kozicz, 2007): (1) acute stress recruits npEW‐Ucn1 neurons in a stressor‐specific fashion (Weninger et al, 1999, 2000; Kozicz et al, 2001; Gaszner et al, 2004); (2) chronic stress elicits a non‐habituating activation of npEW neurons concomitant with strong down‐regulation of Ucn1 expression (Korosi et al, 2005); (3) one of two Ucn1‐deficient mouse lines show increased anxiety‐like behavior, (Vetter et al, 2002), however, another transgenic animal strain displays normal stress‐induced anxiety with increased acoustic startle (Wang et al, 2002). More recently in a third Ucn1 knock‐out mouse line impaired adaptation to repeated restraint and cold stress has been described (Zalutskaya et al, 2007); (4) interestingly the neurochemical make‐up of the npEW in human patients with major depression who had committed suicide appears to be sex‐specifically affected (Kozicz et al, 2008); (5) and finally, CRF‐over‐expressing mice show decreased Ucn1 expression in the npEW (Kozicz et al, 2004), whereas Weninger et al (2000) reported up‐regulation of Ucn1 mRNA in the npEW of CRF‐knockout mice. Interestingly, in both mutant mice, the stress response by the npEW is intact (Weninger et al, 2000; Kozicz et al, 2004).…”
Section: Introductionmentioning
confidence: 99%